Science and nature for the Empire’s Wealth: the baron Eschewege and the mineralogist’s project for Brazil during the century - Doula, Sheila Maria; Slaibi, Thaís Helena de Almeida; Costa, Maria Fernanda de Aguiar (Sociedade & Natureza, 2005)
Science and nature for the Empire’s Wealth: the baron Eschewege and the mineralogist’s project for Brazil during the century